Regulation of Plea Bargaining Policy as a Novelty in Criminal Justice System to Create Effective and Efficient Criminal Law Enforcement: A Study of Ruu Kuhap - Seraphinus Mariano Agung Serman; Umi Rozah (Journal of Law, Politic and Humanities, 2025)
The criminal justice system in Indonesia faces various challenges, such as lengthy judicial processes and case backlogs in the courts. To address these issues, reforms in the criminal justice system are necessary, one of which is the implementation of "Plea Bargaining." This writing is very beneficial as it examines the regulation of plea bargaining in the Draft Criminal Procedure Code (RUU KUHAP). The regulation of plea bargaining in the Indonesian criminal justice system provides benefits in creating an effective and efficient criminal law enforcement process, allowing cases to be resolved more quickly and reducing the burden on the judiciary. Plea Bargaining in the Draft Criminal Procedure Code (RUU KUHAP) is regulated in Article 199 of the Draft Criminal Procedure Code (RUU KUHAP).